The impact of Mergers and Acquisitions on the Financial Performance of Indian Companies - Tandon, Ishita (2009)
Mergers and acquisitions are the one of the quickest and fastest ways of turning a small company into a large enterprise. They are taken as a resolution to various situations. This topic was chosen because of the growing effect the activity of mergers and acquisitions of various sectors in the Indian society. It has been said that it’s a merry time for the Indian corporations. Indian companies are getting involved in cross border mergers and acquisitions due to the increased competition and globalization. Now days the news of Indian cross border mergers and acquisition has become very common.